Possible Point Mutation Sites in LSc, 2ab Poliovirus RNA and a Protein Covalently Linked to the 5′-terminus - Nomoto, Akio; Kajigaya, Sachiko; Suzuki, Keiko; Imura, Nobumasa (Journal of General Virology, 1979)
SUMMARY Poliovirus type 1, vaccine strain (LSc, 2ab), which is a temperature- and actinomycin D-sensitive mutant derived from type 1 Mahoney strain, was grown in HeLa cells in the presence of 32P and a low concentration of actinomycin D. Seven and a half h p.i., genome 32P-RNA was recovered from the purified virion. Analysis of RNase T1 digests of the RNA by two-dimensional gel electrophoresis revealed that three possible point mutation sites exist in the large and unique oligonucleotides in the fingerprint. Neither a capping structure nor a nucleotide such as pppNp, ppNp or pNp, was detected by ion exchange column chromatography at pH 5.0 after digestion of virion RNA with RNase T2. Instead, a 32P-labelled compound, which could be digested with Pronase or proteinase K, was eluted at the void volume of the column. Proteinase K digests of the 32P-labelled compound contained pUp or pU as a single labelled compound, when genome RNA was digested with RNase T2 or nuclease P1, respectively, before digestion with the proteinase. Our data locate possible point mutation sites on the genome of a mutant strain (LSc, 2ab) of type 1 poliovirus and show that a protein (VPg) is covalently bound to the 5′-terminus of the RNA. The protein (VPg) of LSc, 2ab strain migrates faster than capsid protein VP4 (mol. wt. 7000 to 8000) in a polyacrylamide gel and is thus similar to the VPg of the wild-type virus.